One leg of a right triangle is 7 units long, and its hypotenuse is 16 units long. What is the length of the other leg? Round to the nearest whole number.

Answers

Answer 1
Answer:

Answer:

14 units

Step-by-step explanation:

To find the length of the other leg of a right triangle, where one leg is 7 units long and the hypotenuse is 16 units long, use Pythagoras Theorem.

Pythagoras Theorem states that in a right triangle, the square of the length of the hypotenuse (the side opposite the right angle) is equal to the sum of the squares of the lengths of the legs.  

Let the legs of the right triangle be "a" and "b", and the hypotenuse be "c". Therefore:

\begin{aligned}a^2+b^2&=c^2\na^2+7^2&=16^2\na^2+49&=256\na^2+49-49&=256-49\na^2&=207\n√(a^2)&=√(207)\na&=14.3874945...\na&=14\;\sf(nearest\;whole\;number)\end{aligned}

Therefore, the length of the other leg is 14 units (rounded to the nearest whole number).

Answer 2
Answer:

Answer:

7^{2} + x^{2} = 16^{2}

49+x^2=256

x^2=207

x=14.387=14


Related Questions

What is the product of 6x – y and 2x – y + 2?A=8x2 – 4xy + 12x + y2 – 2y B=12x2 – 8xy + 12x + y2 – 2y C=8x2 + 4xy + 4x + y2 – 2y D=12x2 + 8xy + 4x + y2 + 2y
How many red, blues, and greens are there?red, green, blue, blue, red, green, red, green, blue, red red, blue, red, red, blue, red, blue, red, green, red
Identify the appropriate mixed number for the picture shown.A. 11⁄2B. 2 1⁄4C. 2 1⁄2D. 3
Convert the credit card rate to the APR.  Oregon 2/14% per month.
Find the distance between (-1, 4) and (3, 1).

What units could you use to measure the height of a hexagonal prism?cm
cm 2
cm 3
cm 4

Answers

Answer: A. cm

Step-by-step explanation:  The formula for the volume of a hexagonal prism is, volume = [(3√3)/2]a2h cubic units where a is the base length and h is the height of the prism. We can also use the other formula V = 3abh, where a = apothem length, b = length of a side of the base, and h = height of the prism.

no aswer for that question

Whole numbers between 63 and 101

Answers

Answer:

64,81,100

Step-by-step explanation:

Answer: 64,81 and 100

Step-by-step explanation: 8^2=64, 9^2=81 and 10^2=100

Use the unit circle to find cos (-270°)

Answers

Answer:

\cos (-270\degree)=0.

Step-by-step explanation:

We want to find the value of \cos (-270\degree).

Note that;

\cos (-\theta)=\cos (\theta)

This implies that;

\cos (-270\degree)=\cos (270 \degree)

Also 270 degrees is a quadrantal angle.

On the unit circle, \cos (270\degree) is the x-coordinate of the point (0,-1)

Hence, \cos (-270\degree)=0.

Answer:

B.

Step-by-step explanation:

0

The sum of two numbers is 29. If thelarger number is 2 less than three times
the smaller number, what is the smaller
number.

Answers

The smaller number is 7.75.

What is an Equation?

An equation is a mathematical statement formed when two expressions are equated using an equal sign.

The equations are useful in determination of unknown parameters.

The equations are of various types, such as Trigonometric equations, quadratic equations.

The system of equations are used to solve complex problems.

Let the smaller number is x.

The larger number is 2 less than three times the smaller number

Then the larger number is 3x -2

The sum of the two numbers is 29

The sum is the output of the mathematical operation, Addition.

The equation formed is :

3x -2 + x = 29

Grouping the variables and the constants

4x = 31

Dividing both side of the equation by 4

x = 7.75

The value of the smaller number is obtained.

To know more about Equation

brainly.com/question/10413253

#SPJ2

Answer: 7

Step-by-step explanation:

Factor this trinomial. x2 + 2x - 3

A. (x + 3)(x + 1)
B. (x - 3)(x - 1)
C. (x + 3)(x - 1)
D. (x - 3)(x + 1)

Answers

x^2+2x-3=(x+3)(x-1)

Answer:

C  A p e x

Step-by-step explanation:

What is the inverse of the function f(x) = x +3?A. h(x) =1/3 x + 3
B. h(x) = 1/3x – 3
C. h(x) = x – 3
D. h(x) = x + 3

Answers

Answer:

Option C is correct that is h(x)=x-3

Step-by-step explanation:

We have been given a function:

f(x)=x=3

\text{let y}=f(x)

y=x+3

x=y-3

Hence,f^(-1)y=y-3

Therefore, f^(-1)x=x-3

Hence, Option C is correct that is h(x)=x-3

f(x) = x + 3
y = x + 3
x = y - 3

Inverse is h(x) = x - 3